Wooden temple as a marker of the Russian traditional identity - Анна Пермиловская (Проект Байкал)
Wooden architecture is a special independent direction of the Russian traditional architecture. It is represented in Russia in its unique quality and diversity. This is truly a national architecture that has absorbed the mythopoetic and Christian worldview of the people. The concept of “Russian North” reflects the significant “Russianness” of the region. Here, all those perfect forms of wooden architecture were developed to continuously influence the entirety of Russian art for centuries. A wooden temple is the pinnacle of culture, its iconic heritage. The best religious buildings were created and preserved in the North.